Analysis of natural convection for a Casson-based multiwall carbon nanotube nanofluid in a partially heated wavy enclosure with a circular obstacle in the presence of thermal radiation - Ganesh, N. Vishnu; Al-Mdallal, Qasem M.; Öztop, Hakan Fehmi; Kalaivanan, R. (Elsevier, 2022)
Introduction: Nanofluids are considered a better alternative to conventional fluids in many industrial situations and unfolding new opportunities for various applications owing to the optical and thermal properties of additive nanosized materials. Objectives: In this study, the thermal and hydraulic characteristics of a Casson-based (sodium alginate) multiwall carbon nanotube (MWCNT) nanofluid were computationally investigated inside a wavy square enclosure containing a circular-shaped obstacle. The square enclosure comprised two cooled vertical walls and a wavy adiabatic top wall. The central part of the bottom wall comprised a heated wavy structure, and the remaining parts exhibited a flat and adiabatic structure. Methods: The Navier-Stokes (N-S) equations and boundary conditions were established using the non-Newtonian Casson fluid model and Rosseland thermal radiation. The present problem was numerically simulated using the Galerkin finite element method for three types of obstacles, namely, adiabatic, hot, and cold. The impacts of Casson parameter (0.001 <= beta <= 0.1), Rayleigh number (10(3) <= Ra <= 10(6)), nanoparticle volume fraction (0.01 <= phi <= 0.1) and radiation parameter (1 <= Rd <= 4) are analysed. A numerical code validation was performed using the available benchmark results. Results: The characteristics of the convective radiation heat transport were clearly analyzed through the stream function and isotherm plots. For all types of obstacles, the mean Nusselt number along the heated wavy wall increased with the Casson parameter, MWCNT volume fraction, Rayleigh number, and radiation parameter. Conclusion: The heat and flow characteristics of a Casson-based MWCNT nanofluid inside a wavy square enclosure were investigated. The mean Nusselt number was higher (lower) in the presence of cold (hot) obstacles. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of Cairo University.
Keywords: Casson fluid; Carbon nanotubes; Finite element method; Square wavy enclosure; Thermal radiation